2011
DOI: 10.1108/09555341111145762
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the business impact on the natural environment

Abstract: Purpose -The purpose of this paper is to demonstrate the sustainable business practices of Woolworths, a major South African retail chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…Several studies have recently been reported within a business sustainability context, such as: (i) case studies that provide meaningful and valuable contextual insights into this matter (Cambra-Fierro and Ruiz-Benítez, 2011;Dos Santos, 2011;Høgevold, 2011, Høgevold andSvensson andWagner, 2011, 2012); and (ii) models to frame stakeholder considerations, related to the context, and sources, related to the process, (Wagner and Svensson, 2014).…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recently been reported within a business sustainability context, such as: (i) case studies that provide meaningful and valuable contextual insights into this matter (Cambra-Fierro and Ruiz-Benítez, 2011;Dos Santos, 2011;Høgevold, 2011, Høgevold andSvensson andWagner, 2011, 2012); and (ii) models to frame stakeholder considerations, related to the context, and sources, related to the process, (Wagner and Svensson, 2014).…”
Section: Research Implicationsmentioning
confidence: 99%
“…The authors were, however, able to uncover models that framed the contemplation of stakeholders by companies when sustainability is concerned (Wagner and Svensson, 2014). The authors were furthermore able to discover a number of case studies that delivers telling and significant understandings of the BUSINESS SUSTAINABILITY IN CONTEXT context within which companies undertake sustainable business practices (Cambra-Fierro and Ruiz-Benítez, 2011;Dos Santos, 2011;Høgevold, 2011, Høgevold andSvensson andWagner, 2011, 2012) The degree to which companies contemplate or consider their stakeholders when it comes to sustainability are, however, inadequate when various sectors and industries are concerned. In fact, there is to the authors knowledge only one previous study beyond case study research that has empirically studied focal companies' considerations of other stakeholders in supply chains in connection to their business sustainability efforts based upon a broad spectrum of businesses.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of approaches were used by researchers while studying sustainability in retail, which include case study approach (Dos Santos, 2011), content analysis (Fulton & Eun Lee, 2013), and interviews and observations (Lehner, 2015). While most of the existing research focuses on sustainability practices of retailers in various sectors (viz., grocery, food, and garment) in both online and physical formats, considerable amount of research has been done on leveraging the sustainable practices for marketing and branding (e.g., Ilić, Stanković, & Ilić, 2013; Lehner & Halliday, 2014; Miller & Merrillees, 2013; Stuart, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
“…GreenChoice), contribute to making a 'business case' for biodiversity conservation. 76 The notion of a business case often finds resonance and expression in corporate stewardship 'sustainability journeys' of retailers 123 , although there are possible weaknesses in using 'journey' as a metaphor for measuring progress in sustainability 124 .…”
Section: Motivations and Mechanismsmentioning
confidence: 99%